Engineering d‐p Orbital Hybridization in Single‐Atom Metal‐Embedded Three‐Dimensional Electrodes for Li–S Batteries. Issue 44 (27th September 2021) - Han, Zhiyuan; Zhao, Shiyong; Xiao, Jiewen; Zhong, Xiongwei; Sheng, Jinzhi; Lv, Wei; Zhang, Qianfan; Zhou, Guangmin; Cheng, Hui‐Ming
Abstract: Single‐atom metal catalysts (SACs) are used as sulfur cathode additives to promote battery performance, although the material selection and mechanism that govern the catalytic activity remain unclear. It is shown that d‐p orbital hybridization between the single‐atom metal and the sulfur species can be used as a descriptor for understanding the catalytic activity of SACs in Li–S batteries. Transition metals with a lower atomic number are found, like Ti, to have fewer filled anti‐bonding states, which effectively bind lithium polysulfides (LiPSs) and catalyze their electrochemical reaction. A series of single‐atom metal catalysts (Me = Mn, Cu, Cr, Ti) embedded in three‐dimensional (3D) electrodes are prepared by a controllable nitrogen coordination approach. Among them, the single‐atom Ti‐embedded electrode has the lowest electrochemical barrier to LiPSs reduction/Li2 S oxidation and the highest catalytic activity, matching well with the theoretical calculations. By virtue of the highly active catalytic center of single‐atom Ti on the conductive transport network, high sulfur utilization is achieved with a low catalyst loading (1 wt.%) and a high area‐sulfur loading (8 mg cm −2 ). With good mechanical stability for bending, these 3D electrodes are suitable for fabricating bendable/foldable Li–S batteries for wearable electronics. Abstract : A descriptor, the d–p hybridization state between single‐atom metal catalysts (SACs) and sulfur species, is proposed to guide the design of SACs for Li–S batteries. The large‐sized and flexible 3D electrodes with optimized SACs achieve high specific energy with low catalyst loading and high sulfur loading. The good mechanical stability for bending also shows potential for fabricating bendable/foldable Li–S batteries.